Effect of Nb contents on the passivation behavior of high-strength anti-seismic rebar in concrete environments - Zeyun Zeng; Shangjun Gu; Jie Wang; Fulong Wei; Xiang Xie; Zhiying Li; Hui Yang; Changrong Li (npj Materials Degradation)
Abstract In this study, the surface analysis, cross-section analysis and electrochemical analysis were used to explore the formation mechanism of Nb contents on the passive film of high-strength anti-seismic rebar in simulated concrete pore solution. The passivation experiments confirmed that the addition of Nb promoted the stability and compactness of surface passive film of Nb-containing rebar, and the passivation efficiency of Nb-containing rebar was stronger than that of CS rebar. Firstly, with the decreases of pH, the increases of Nb promoted that the outer layer of the passive film were mainly composed of Fe oxides and Fe oxyhydroxides, the inner layer were mainly composed of Fe oxides and Nb oxides. Secondly, the increases of Nb were beneficial to the formation of Nb oxides, which enhanced the passivation rate of the passive film and inhibited the degradation of Fe oxides, thus enhancing the thickness of surface passive film of Nb-containing rebar.